Identification and Functional Characterization of Squamosa Promoter Binding Protein-Like Gene TaSPL16 in Wheat (Triticum aestivum L.) - Cao, Rufei; Guo, Lijian; Ma, Meng; Zhang, Wenjing; Liu, Xiangli; Zhao, Huixian (Frontiers in Plant Science, 2019)
Wheat (Triticum aestivum L.) is one of the most important crops in the world. Squamosa promoter binding protein-like (SPL) proteins are plant specific transcript factors and play critical roles in plant growth and development. The functions of many SPL gene family members were well-characterized in Arabidopsis and rice, in contrast, research on wheat SPL genes is lagging behind. In this study, we cloned and characterized TaSPL16, an orthologous gene of rice OsSPL16, in wheat. Three TaSPL16 homoeologs are located on the short arms of chromosome 7A, 7B, and 7D, and share more than 96% sequence identity with each other. All the TaSPL16 homoeologs have three exons and two introns, with a miR156 binding site in their last exons. They encode putative proteins of 407, 409 and 414 amino acid residues, respectively. Subcellular localization showed TaSPL16 distribution in the cell nucleus, and transcription activity of TaSPL16 was validated in yeast. Analysis of the spatio-temporal expression profile showed that TaSPL16 is highly expressed in young developing panicles, lowly expressed in developing seeds and almost undetectable in vegetative tissues. Ectopic expression of TaSPL16 in Arabidopsis causes a delay in the emergence of vegetative leaves (3-4 days late), promotes early flowering (5-7 days early), increases organ size, and affects yield-related traits. These results demonstrated the regulatory roles of TaSPL16 in plant growth and development as well as seed yield. Our findings enrich the existing knowledge on SPL genes in wheat and provide valuable information for further investigating the effects of TaSPL16 on plant architecture and yield-related traits of wheat.